Rancang Bangun Aplikasi Edukasi Interaktif Cerita Rakyat ‘Keong Mas’ Berbasis Augmented Reality Menggunakan Unity 3D - Asa Yuaziva (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
The purpose of this research is to create an interactive Augmented Reality (AR)-based educational application that can display the Indonesian folktale